The Evolution of Animal Research in Ancient Mediterranean Society - Fritz, Sylvia (My University, 2024)
For my honors project, I sought to combine my bachelor’s degree, biology, with my minor, in classics. I plan to go into research in the future, and I thought it would be interesting to see how research came to be what it is today. A lot of the fundamental ideas of research originated in ancient Mediterranean society, though it looked much different than the typical thesis paper seen in modern-day research. In this project, I examined the earliest developments of the studies of animals in ancient Mediterranean society and how it developed and evolved. I read several different works by scholars in the ancient Mediterranean region spanning from 300 B.C.E to 200 C.E. The three researchers I decided to focus on included Aristotle, Pliny the Elder, and Galen. Aristotle in some of his lecture notes about “The History of Animals” discussed systems of organization and proposed theories of the origins of animals and other aspects of nature. Pliny the Elder wrote a collection of thoughts about animals, arranged into what is considered to be the first encyclopedia called Natural History. I also read several excerpts and summaries of Galen’s anatomical research on barbery apes and pigs. He performed vivisections on these animals to figure out many fundamental ideas of anatomy in both humans and animals from this animal research. All of these were able to provide a narrative of the evolution of written research in animals. This project was incredibly interesting and provided a lot of context for the world I am about to be a part of. I believe one of the most important aspects of life is knowing history, and I feel more prepared for my future career in research having gained a better understanding of where different aspects of research originated.